“Sustainable pastoral practices within the continuous reality of the COVID-19 pandemic within the Church of Pentecost, in South Africa” - Anyimadu, Bernard Boakye (Stellenbosch : Stellenbosch University, 2023)
Thesis (MTh)--Stellenbosch University, 2023.